Strategi Keamanan Maritim Indonesia terhadap Maritime Piracy di Laut Sulu Tahun 2016 - Saraswati, Ayu Laksmi; Pinatih, Ni Komang Desy Arya (Department of International Relations, Brawijaya University, 2020)
The Sulu Sea, one of Indonesia's seas located in the strategic area of ALKI II (Indonesian Archipelagic Sea Lane), directly borders Malaysia and the Philippines. As a busy trade route, the sea is also vulnerable to threats such as maritime piracy. This research aims to see Indonesia's maritime security strategy in the Sulu Sea over maritime piracy cases in the area during 2016. In this research, the writer uses the Maritime Security concept proposed by Chris Rahman to explain Indonesia's maritime security strategy in the Sulu Sea. The author using three variables, including (1) security of the sea itself: conservation and protection; (2) ocean governance; (3) maritime border protection; (4) military activities at sea, and (5) security regulation of the transport marine system in their correlation with each other. The author then concludes that out of five variables, only two are suitable and effective for implementing piracies in the Sulu Sea, namely maritime border protection and military activities at sea.